Forms of Customary Respect in the Tana Language in Traditional Wedding Ceremonies in Amahai, Central Maluku - Telehala, Gratia Priskila; Lelapary, Heppy Leunard (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to delineate the manifestations of customary respect in the Tana language during traditional wedding rites in Amahai State, Central Maluku. This research's theoretical merits include its potential to enhance the Tana language notion from both linguistic and oral literary viewpoints. The practical advantage lies in comprehending the expressions of traditional respect, including those in the Tana language during wedding rites in Amahai State, Central Maluku. The employed study methodology is qualitative, conducted in Amahai State, Central Maluku, utilizing data sources that include the King of Amahai State and three traditional leaders. The methodologies for data collecting include observation, documentation, field notes, and interviews. Traditional expressions of respect constitute a variant of the Tana language employed in customary rituals in Central Maluku, often utilized at both the commencement and conclusion of the Tana language communication process during these events. Research on the manifestations of customary respect in the Tana language during traditional wedding rites in Amahai State, Central Maluku. The investigated traditional mananol ceremony was discovered to take place at the Topisila residence, Hari Lernaya Teung Mansama Leparisa. In the Amahai language, it is referred to as the Aruno Lahitolo Mananol Ceremony, a traditional mananol ceremony organized into three phases. The initial phase is the preparatory stage. The second step involves the procession of the Aruno Lahitolo Mananol traditional ceremonial. The third step is the concluding phase of the traditional event, conducted in the Baileu Negeri Amahai in Central Maluku.